Cultivating Awareness from an Early Age: Education and Social Action - Rutinaias Haholongan; Zulkarnaini Zulkarnaini; Bayu Pratama; Sabilla Pancarani Gusti Tanjung; Andi Wijaya (Entrepreneurship and Community Development, 2026)
Instilling values of caring, empathy, and cooperation from an early age is essential in shaping future generations’ character. A major challenge faced by the Gondangdia RPTRA community and its partners is the limited availability of structured, enjoyable, and sustainable educational activities that support children’s social character, creativity, communication skills, and sense of community. Children aged 8–10 need a safe and accessible learning environment that balances cognitive, motor, social, and emotional development. To address this issue, educational and social activities were organized at Gondangdia RPTRA in collaboration with the SEKOCI community. As a child-friendly public space, the RPTRA provides an ideal environment for interactive learning. The program included collaborative games, creative plaster coloring, and basic English learning activities. These methods encouraged children to learn through play, communication, teamwork, and creative expression. The activities improved children’s social sensitivity, self-confidence, creativity, and community awareness. In addition, the program strengthened partner involvement in providing positive mentoring, enabling character-building activities to continue sustainably through future community initiatives.